2014
DOI: 10.13075/mp.5893.2014.025
|View full text |Cite
|
Sign up to set email alerts
|

Do Double Gloves Protect Against Contamination During Cannulation of Blood Vessels? A Prospective Randomized Study

Abstract: StreszczenieWstęp: Nienaruszone rękawiczki medyczne zabezpieczają personel medyczny przed kontaktem z płynami fizjologicznymi pacjenta. Chronią w ten sposób osobę udzielającą pomocy przed kontaminacją skóry dłoni potencjalnie skażonym materiałem biologicznym. Celem pracy jest ocena występowania przekłuć, perforacji i uszkodzeń rękawiczek medycznych podczas kaniulacji naczyń obwodowych. Materiał i metody: W badaniu przeanalizowano 303 pary rękawiczek użytych podczas kaniulacji naczyń obwodowych w warunkach symu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…In this study the middle finger an ring finger on the left hand of the surgeon were most likely part of glove to be punctured or torn. Other studies have shown similar results [4,9,17]. That is because surgeons usually hold sharp tools in the right hand, and it can lead to accidental damage to the left glove.…”
Section: Glove Failure In Elective Thyroid Surgery O R I G I N a L P mentioning
confidence: 53%
See 1 more Smart Citation
“…In this study the middle finger an ring finger on the left hand of the surgeon were most likely part of glove to be punctured or torn. Other studies have shown similar results [4,9,17]. That is because surgeons usually hold sharp tools in the right hand, and it can lead to accidental damage to the left glove.…”
Section: Glove Failure In Elective Thyroid Surgery O R I G I N a L P mentioning
confidence: 53%
“…They protect against bloodborne pathogens, such as human immunodeficiency virus (HIV), hepatitis B virus (HBV) or hepatitis C virus (HCV). The risk of acquiring a virus from 1 percutaneous needle stick is 0.3-0.4% for HIV, 6-30% for HBV, and 2.7-10% for HCV [2][3][4][5]. Compared to other clinical fields, surgeons are at a higher risk of glove perforation due to the frequent manipulation of surgical instruments and the use of sharp tools during operative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…22 Anxiety, stress, being in a hurry, fatigue and carelessness may also increase the risk of NSI. 15,23,24 Studies conducted by Osazuwa-Peters et al suggest that most often injuries occur due to a lapse in concentration (14.8%) and unexpected patient movement (12.3%). …”
Section: Risk Factors For Exposurementioning
confidence: 99%
“…25 Wearing two pairs of gloves significantly reduces the risk of the inner gloves' perforation and is far safer for the operator than a single pair, but similar to one pair of thicker, orthopedic gloves. 23,25 Even more protection is ensured by triple gloving, knitted outer gloves and glove liners. 25 Most of the studies do not show a significant relationship between double gloving, lower dexterity of the operator and more perforations of gloves, but in a group of medical rescuers, double gloving significantly reduced dexterity.…”
Section: Factors Decreasing the Risk Of Exposurementioning
confidence: 99%
See 1 more Smart Citation